Disease screening and antimicrobial activity of stingless bees (Heterotrigona itama Cockerell and Geniotrigona thoracica Smith) in Malaysia - Amirthalingam, Vinailosni (2022)
Honeybees are vulnerable to diseases and pests. The presence of pests and diseases in honeybee colonies had caused the honey industry to face many difficulties in the past. Stingless bees are the alternative producer for honey production. The occurrence of honeybee diseases in stingless bees have been reported in oversea and the health status of stingless bees in Malaysia is unknown. Thus, this was the first attempt in Malaysia to screen the health of stingless bees to see if they were free from honeybee diseases. Adults of Heterotrigona itama and Geniotrigona thoracica were collected from eight different farms and tested negative to seven known honeybee diseases. During the sampling, one G. thoracica colony at the Department of Plant Protection, UPM was detected having white mycelia on its propolis, and another H. itama colony at the Infoport Halal Hub, UPM was collapsed with white dust covered on the propolis. Isolation of the fungi were done, and pure colonies were obtained. The fungus isolated from the G. thoracica colony was confirmed as Lasiodiplodia theobromae, while the fungus isolated from H. itama colony was confirmed as Aspergillus caelatus by morphological and molecular identification. A pathogenicity test was conducted using both the fungus species and last instar larvae the stingless bees. The LC50 value of 9.16 x 103 conidia/μl was recorded in H. itama larvae infected with L. theobromae. It was not pathogenic to G. thoracica (22% mortality). When H. itama and G. thoracica were inoculated with A. caelatus, 100% mortality was obtained in both stingless bee species. The LC50 value were 7.58 x 103 conidia/μl for H. itama and 6.24 x 103 conidia/μl for G. thoracica. A. caelatus was confirmed pathogenic to both H. itama and G. thoracica. Antimicrobial susceptibility test was carried out using the hemolymph of the last instar larvae of H. itama to test against A. caelatus. No inhibition was observed in the treatment with either induced or non-induced hemolymph at the end of the broth microdilution assay. The positive control, intraconazole, had recorded 70.23% inhibition. Again, A. caelatus was confirmed very pathogenic to H. itama and the insect host immunity was able to fight against A. caelatus. The antimicrobial susceptibility test was not carried on G. thoracica with both fungus species and H. itama with L. theobromae as the bee colonies were stolen during the Covid-19 pandemic.